(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2026)
Tangkunei Village, located in the Tumpaan District of South Minahasa Regency, faces significant challenges in clean water distribution. The primary issues include unequal water flow due to topographical constraints, suboptimal pipeline network design, and a lack of flow control systems. This community service program aims to optimize the clean water distribution system through the implementation of appropriate technology and community empowerment. The methods employed involved a technical assessment followed by the installation of flow control valves and automatic taps, the implementation of a flow zoning system, and comprehensive technical training for residents. The program resulted in the successful balancing of water pressure across different zones, ensuring equitable access for previously underserved areas. Furthermore, the establishment of a village-level management team and the execution of maintenance workshops have enhanced the community’s capacity to manage the water network independently. It can be concluded that the application of simple, cost-effective technology combined with community capacity building effectively resolves water distribution disparities in geographically challenging areas.